Pressure-transient behavior in class III hydrate reservoirs. (1st March 2019) - Hou, Jian; Zhao, Ermeng; Liu, Yongge; Ji, Yunkai; Lu, Nu; Liu, Yueliang; Li, Huazhou Andy; Bai, Yajie
Abstract: Hydrate reservoirs generally have some unique characteristics such as hydrate dissociation and reformation, permeability change, which may result in quite different pressure-transient behavior from that in conventional reservoirs. In this work, we develop the pressure-transient analysis method for Class III hydrate reservoirs. By establishing a 2D cylindrical model, we then conduct a pressure buildup test and five flow regimes are identified according to the exhibited characteristics observed from the pressure-transient curves. Furthermore, sensitivity analysis is conducted to study the effects of initial reservoir pressure, initial reservoir temperature, permeability reduction exponent, BHP (bottom-hole pressure), and production time on pressure-transient behavior. We identify five flow regimes on the pressure-transient curves. Due to the dissociation of gas hydrate, the first regime is dominated by the non-uniform distribution of permeability, and the pressure derivative curve exhibits an upward straight line. We identify a " V -shaped" valley in the second regime with a peak in the third regime, which suggests the occurrence of hydrate reformation near the wellbore. Such characteristics exhibited in the three regimes are unique to hydrate reservoirs. In addition, the methodology proposed in this study is successfully applied to analyze the actual well testing data obtained from the Malik hydrate reservoir in Canada. Highlights: The pressure-transient analysis method is proposed for gas hydrate reservoirs. Five flow regimes are identified on pressure-transient curves in Class III hydrate reservoirs. Pressure-transient behaviors in Class III hydrate reservoirs are fully analyzed. Key parameters on pressure-transient behaviors are analyzed.